Stimulasi Gangguan Artikulasi Anak Usia 4-6 Tahun Melalui Permainan Ampar-Ampar Pisang di TK Buah Hati Kutai - Candra Dewi Kurniasari; Heppy Liana; Yeni Aslina (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
Abstract Articulation disorder is a speech impairment in children characterized by difficulty in correctly pronouncing phonemes, thus requiring stimulation according to developmental stages. This study aims to examine the implementation of articulation disorder stimulation in children aged 4-6 years through the Ampar-Ampar Pisang game at Buah Hati Kindergarten, Kutai Kartanegara, as well as the supporting and inhibiting factors. The research employed a qualitative case study method with five children as research subjects. Data were collected through non-participant observation, in-depth interviews, and documentation, then analyzed through reduction, presentation, and conclusion drawing, with validity tested using source and technique triangulation. The results showed that stimulation was carried out in four stages: introduction, play, repetition, and evaluation. In the introduction stage, educators build emotional readiness; in the play stage, children actively play while singing; lyric repetition strengthens articulation; and evaluation is conducted to record children’s articulation progress. Supporting factors for stimulation include a cheerful play atmosphere, educator consistency, regular play routines, and parental involvement. Inhibiting factors include differences in character, children’s emotional levels, and an unconducive environment. The study concludes that enjoyable play fosters children’s confidence and motivation in pronouncing difficult phonemes. From a neuroscience perspective, songs and movements activate auditory, motor, and emotional areas simultaneously, strengthening neural pathways involved in articulation development. The novelty of this research lies in utilizing the Ampar-Ampar Pisang game as an articulation stimulation medium integrated with neuroscience and contextual learning approaches, which remain rarely explored in early childhood education.